Urinary Modified C-Reactive Protein is Closely Associated with Tubulointerstitial Lesions in Lupus Nephritis - Mo Yuan; Xiao-ling Liu; Ying Tan; Feng Yu; Ming-hui Zhao (Hindawi Limited, 2023)
Objective. Modified C-reactive protein (mCRP) is known to be involved in the upregulation and amplification of the local inflammatory response. This study investigated the circulating and local levels of mCRP and their relevance to clinicopathological features in patients with lupus nephritis. Methods. Ninety-five patients with renal biopsy-proven lupus nephritis and 30 normal controls were enrolled in this study. Plasma and urinary mCRP were screened by enzyme-linked immunosorbent assay (ELISA). The renal deposition of mCRP was detected by immunohistochemistry and immunofluorescence staining. A human proximal tubular epithelial cell line (HK2 cells) was incubated with purified IgG from lupus nephritis, and the production of CRP by HK2 cells was further evaluated. Results. Plasma and urinary levels of mCRP increased significantly in patients with lupus nephritis compared with normal controls (P=0.013, P<0.001, respectively). The urinary mCRP levels were associated with interstitial inflammatory cell infiltration (r = 0.514, P<0.001) and interstitial fibrosis (r = 0.270, P=0.008). The ROC-AUC of the urinary mCRP levels for diagnosing tubulointerstitial lesions was 0.766. The urinary mCRP levels were closely associated with poor outcomes (HR: 1.204, 95% CI: 1.029-1.409, P=0.020). However, no correlations were found of the plasma mCRP levels with clinicopathological data or the prognosis of lupus nephritis. CRP was mostly deposited in the renal tubules in patients with lupus nephritis, and the expression of CRP was significantly correlated with tubulointerstitial lesion indices. Immunofluorescence staining showed that mCRP could colocalize with IgG in tubules. Lupus nephritis-derived IgG could induce CRP production by HK2 cells. Conclusion. Urinary mCRP levels were significantly increased, and urinary mCRP might be a biomarker for tubulointerstitial lesions in patients with lupus nephritis. Renal CRP could be produced by tubular epithelial cells after stimulation by lupus nephritis-derived IgG, and the local presence of mCRP might play a critical role in the development of tubulointerstitial lesions.